Parasympathetic Nerve Function Status During Different Phases Of Menstrual Cycle In Healthy Young Women - Choudhury, Rama; Jahan, Nasim; Sultana, Nayma; Akter, Rezina; Khanum, Ayesha Akhter (Journal of Bangladesh Society of Physiologist, 2012)
Background: Autonomic nerve function status may be changed during follicular and late luteal phases of menstrual cycle due to fluctuations of serum estrogen and progesterone levels. This alteration in autonomic nerve functions may affect cardiovagal control and usually associated with decreased parasympathetic activity in late luteal phase. Objective: To observe the parasympathetic nerve function status during follicular and late luteal phases of menstrual cycle and also their relationships with serum estrogen and progesterone levels in healthy young women. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st January 2009 to 31st December 2009. A total number of thirty (30) apparently healthy unmarried women age ranged from 20-25 years were studied in both follicular (phase A, control) and late luteal (phase B, study) phases of menstrual cycle. Simple autonomic nerve function tests like heart rate (HR) response to valsalva maneuver (valsalva ratio), HR response to deep breathing, HR response to standing (30th:15th ratio) were done to assess parasympathetic activity and serum estrogen and progesterone levels were also measured by AxSYM method. All these tests were performed in both follicular and late luteal phases of menstrual cycle of the same subject. Data were analysed by paired student’s ‘t’ test and Pearson’s correlation coefficient test as applicable. Results: Mean values of both HR response to valsalva ratio and HR response to standing (30th:15 th ) were non-significantly decreased but HR response to deep breathing was significantly (p<0.05) decreased in late luteal phase than those of follicular phase. Conclusion: From this study it can be concluded that parasympathetic activity is decreased in late luteal phase of menstrual cycle. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9759 JBSP 2011 6(2): 100-107